Patients responses to diagnoses of mental disorders: Development and validation of a reliable self‐report measure. Issue 1 (12th September 2020) - Schnell, Thomas; Kehring, Anja; Moritz, Steffen; Morgenroth, Olaf
Abstract: Objectives: Psychiatric patients are regularly informed about diagnoses. Treatment guidelines assume that informing patients fosters functional coping processes, but few research exists on how patients respond. Thus, the objective was to develop a standardized self‐report measure to assess patients reactions to diagnoses. Methods: Fifty nine items were generated based on a qualitative study. The process of item selection and determination of the factor structure were performed on a sample of 252 patients: Results of an explorative factor analysis with a randomly split sub‐sample 1 were cross‐validated by confirmatory factor analysis on sub‐sample 2. The revised 26‐item instrument was revaluated using data from an independent sample of 1.271 patients with different diagnoses. Results: Three functional and three dysfunctional processing styles emerged from the analyses and provided good model fit in the revaluation study (TLI = 0.935; CFI = 0.943; RMSEA = 0.051; SRMR = 0.048). Variance‐analytical calculations and post hoc analyses revealed significant differences among diagnoses with regard to coping styles, such as schizophrenia was associated with self‐stigmatization and anorexia nervosa showed pronounced over‐identification. Overall, various diagnosis‐dependent specifics were found. Conclusions: As patients reactions to diagnoses vary substantially, their formation, impact on treatment and overall cause should be investigated in further studies.